Optimising a Nutritious, Affordable, and Culturally Acceptable Diet for Ghanaian Adolescents Using Linear Program - Donkor, Leticia; Essien, Emmanuel; Vlaeminck, Hanne; Vasco, Juan-Pablo; Nykänen, Esa-Pekka; Sintim, Henry Ofosuhene; Affrifah, Nicole Sharon; Saalia, Firibu Kwesi (Enviro Research Publishers, 2026)
Nutrition is key for adolescents because it directly impacts their health and long-term well-being. As this demographic undergoes rapid growth and development, the significance of proper nutrition is paramount. However, ensuring adequate adolescent nutrition is complex due to economic constraints in the developing world. Considering the socioeconomic difficulties that can prevent access to nutritious food, this study aimed to create low-cost, culturally acceptable food baskets that meet nutritional and socio-cultural requirements, using locally available ingredients in Ghana. A linear programming approach was used to identify the set of ingredients where the total cost of the food basket was considered as the objective function to be minimised. Locally available food items with their prices and nutrient composition were used to obtain the optimised food baskets for the defined target groups at minimum cost. The optimised food baskets met Food and Agriculture Organisation (FAO) & World Health Organisation (WHO) and the Institute of Medicine’s nutrient requirements for adolescent males and females within specified limits. The estimated costs of the proposed ingredients were at a minimum 15.70 and 15.57 per food basket, respectively for adolescent males and females. Each of the food baskets designed for adolescent males and females contained 15 food items, and their nutrient requirements stayed within the lower and upper levels defined.